Incidence and survival of Lung Cancer: A retrospective population-based cohort (Monastir, Tunisia: 2002–2022) - Wafa Dhouib; Amani Maatouk; Cyrine Bennasrallah; Mariem Kacem; Syrine Doghri; Ahmed Trigui; Mounib Bouazizi; Lamis Milad; Manel Ben Fredj; Ines bouanene; Hela Abroug; Naceur Rouatbi; et al. (PLoS ONE, 2025)
Introduction Lung cancer (LC) remains one of the most lethal malignancies worldwide. In Tunisia, LC population-level data is limited. This study aimed to estimate the incidence, mortality, trends burden and survival outcomes of LC over two decades in Monastir (Tunisia). Methods We conducted a retrospective population-based cohort including all LC patients diagnosed between 2002 and 2014 in the governorate of Monastir, with follow-up until 2022. Age-standardized incidence and mortality rates (ASIR and ASMR) were calculated and expressed per 100,000 Person-Years (PY). Trends were analyzed using Joinpoint regression to determine Annual Percent Change (APC). Disability-Adjusted Life Years (DALYs), Years of Life Lost (YLL), and Years Lived with Disability (YLD) were computed. Survival analysis was performed using Kaplan–Meier estimates, and multivariable Cox proportional hazards regression was used. Results LC ASIR per 100,000 PY was 18.37 (95% CI: 15.1–21.7), 33.63 (29.3–38.0) in males, and 4.50 (2.75–6.41) in females. ASMR per 100,000 PY was 12.33 (9.2–15.84), 24.84 (19.9–29.82) in males, and 2.0 (0.6–3.42) in females. Incidence showed a significant upward trend (APC 8.23%, 95% CI: 2.66–16.12), particularly in females (APC 17.99%, 95% CI: 9.86; 33.27). Projected ASIRs were 43.7 per 100,000 PY in 2025 (95% CI: 37.1–50.3) and 64.7 per 100,000 PY in 2030 (95% CI: 56.7–72.7). DALYs attributable to LC were 1,328 per 100,000 PY, comprising 1,198.8 YLLs and 129.2 YLDs. One-year and five-year survival rates were 43.2% (95% CI: 36.6–49.8) and 22.1% (95% CI: 17.4–26.8), respectively, with a median survival of 10 months (95% CI: 8.9–11.0). Survival was higher among females, younger patients (<65 years), and those diagnosed after 2009, with an improved median survival. Conclusion LC incidence and mortality are rising, with low survival and a substantial burden of premature mortality, highlighting the urgent need for population-based prevention programs.